Pengaruh Kepemimpinan Instruksional Kepala Sekolah Terhadap Komitmen Guru - Diah Ayu Sucitra; Hasan Hariri (Program Studi Manajemen Pendidikan, 2023)
The study aims to examine the effect of instructional leadership on organizational commitment. This research uses a quantitative approach. The population in this study were all public elementary school teachers in Pringsewu Regency with a total of 2,736 teachers. Sampling using cluster random sampling technique and obtained 350 samples. The data analysis technique in this study used simple regression. The research findings show that there is a positive influence of head instructional leadership on organizational commitment.